2015
DOI: 10.1159/000431228
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Immune Response to the Shrimp Allergen Tropomyosin: Histological and Immunological Analysis in an Animal Model of Shrimp Tropomyosin Hypersensitivity

Abstract: Background: Shellfish hypersensitivity is among the most common food allergies. A murine model of IgE-mediated shrimp allergy has been established in our laboratory. The aim of this study is to determine the intestinal histological changes and cytokine expression profile of this model sensitized with the major shellfish allergen tropomyosin. Methods: Female Balb/c mice orally sensitized and challenged with recombinant tropomyosin were sacrificed. Continuous sections of duodenum, jejunum and ileum were prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…There are 3 previous elegant studies that reported on the development of shrimp allergy and 1 on mud crab allergy using mouse models with BALB/c and C3H/HeJ mice [25,26,27,28]. Thus, Capobianco et al [27] reported a shrimp tropomyosin allergy mouse model using C3H/HeJ mice with oral exposure to purified shrimp tropomyosin along with cholera toxin adjuvant; their readouts of allergenicity included sIgE (OD values; no titers), spleen-cell IL-4 production and systemic anaphylactic symptom scores upon OC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are 3 previous elegant studies that reported on the development of shrimp allergy and 1 on mud crab allergy using mouse models with BALB/c and C3H/HeJ mice [25,26,27,28]. Thus, Capobianco et al [27] reported a shrimp tropomyosin allergy mouse model using C3H/HeJ mice with oral exposure to purified shrimp tropomyosin along with cholera toxin adjuvant; their readouts of allergenicity included sIgE (OD values; no titers), spleen-cell IL-4 production and systemic anaphylactic symptom scores upon OC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Capobianco et al [27] reported a shrimp tropomyosin allergy mouse model using C3H/HeJ mice with oral exposure to purified shrimp tropomyosin along with cholera toxin adjuvant; their readouts of allergenicity included sIgE (OD values; no titers), spleen-cell IL-4 production and systemic anaphylactic symptom scores upon OC. Lam et al [25] and Leung et al [26] reported another shrimp tropomyosin allergy model using recombinant protein and BALB/c mice using intragastric exposure with cholera toxin adjuvant [25,26]. Readouts of allergenicity included sIgE responses (OD values; no titers), spleen-cell IL-4 responses, oral allergen-induced symptom scores and histopathological changes in the gut.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we focused on allergic symptoms, rMet e 1-specific antibodies, and histological and immunological changes in the gastrointestinal tract where some of the major clinical symptoms of shrimp allergy occur [11], with an emphasis on the induction of intestinal T reg cells. Our results from this study provide an insight into the effector mechanisms of AIT with different dosages and facilitate the determination of optimal AIT dosing for shrimp allergy.…”
Section: Introductionmentioning
confidence: 99%